MODELS OF DEFICIENCIES AND PRINCIPLES OF ANALYSIS OF TECHNICAL DATA OF MICROPROTORCESSOR DEVICES (Conferencea, 2021)
In almost all data transmission systems of microprocessor devices their widespread application poses problems in ensuring their reliable operation [1-3]. Microprocessor devices are devices based on highly integrated circuits, microprocessors, or single-chip microcontrollers.